Pattern recognition and image analysis 5th Iberian Conference, IbPRIA 2011, Las Palmas de Gran Canaria, Spain, June 8-10, 2011. Proceedings - Vitrià, Jordi; Sanches, João Miguel; Hernández, Mario; SpringerLink (Online service). (Berlin Springer, 2011)
This volume constitutes the refereed proceedings of the 5th Iberian Conference on Pattern Recognition and Image Analysis, IbPRIA 2011, held in Las Palmas de Gran Canaria, Spain, in June 2011. The 34 revised full papers and 58 revised poster papers presented were carefully reviewed and selected from 158 submissions. The papers are organized in topical sections on computer vision; image processing and analysis; medical applications; and pattern recognition.
Electronic reproduction.
Keywords: Optical pattern recognition -- Congresses; Pattern recognition systems -- Congresses; Image processing -- Congresses; Computer vision -- Congresses; Electronic books